Type 1 diabetes in low and middle-income countries - Tanzania a streak of hope - Ludvigsson, Johnny; Edna, Majaliwa; Ramaiya, Kaushik (Frontiers in Endocrinology, 2023)
In several of the Low and Middle Income countries , many patients with Type 1 diabetes (T1D) are most probably not diagnosed at all which may contribute to their low incidence. As an example of a country with low income and poor resources, we have chosen to study T1D in children/young people in Tanzania. The incidence in several areas is low. However, a lot of data are often missing at studied clinics and therefore the incidence might be higher, and with increased awareness in recent years the number of patients has increased many-folds. Most patients present with typical symptoms and signs of T1D, and a high proportion with plausible ketoacidosis , although this proportion has decreased from about 90% to about 40% in recent decades. Many patients have poor blood glucose control, and complications often develop already after short diabetes duration. In recent years resources have increased, awareness has increased and diabetes clinics started where staff has got training. Several facts give hope for the future.